Pengaruh Koordinasi Camat Tehadap Keberhasilan Pembangunan di Kecamatan Singkil Kota Manado - Maryani, Ika; Rumapea, Patar; Rompas, Sonny (Sam Ratulangi University, 2015)
Abstract: The coordination in the implementation of development carried out by the Head in hiscapacity as head of the administrative area of the District, who was given the task to coordinate theactivities of an operational nature. In conjunction with the coordination function, then Head efforts areundertaken on an ongoing basis can create a good working relationship with a subordinate even toinstitutions / agencies diwilayahnya partners, such as the urban / rural development that support theimplementation. In accordance with the characteristics of the problems examined and the formulationof hypotheses that have been proposed previously, then the relevant quantitative approach to theapplication of the method used descriptive (Nazir 1988; Koentjaraningrat, 1997); and explanatorysurvey (Vredenbreght, 1981). Distribution of respondents as described in Table 3 it can be seen that ofthe 80 respondents were interviewed about the application function camat coordination in theimplementation of the development, there were about 45 or Â± 56.3% of respondents stated that theapplication functions camat coordination in the implementation of development in the District Singkilis in the category